Modelo termomicroestrutural para determinação de variáveis operacionais e metalúrgicas para utilização em simulação e/ou controle na laminação a quente de aços carbono e microligados - Machado, Marcelo Lucas Pereira (2005)
Due to the strong relationship between the microstructural changes and the mechanical properties of steel in a hot strip mill, the development of models that take into consideration metallurgic steel properties and operational variables with the objective of optimizing the process has become more necessary. The developed thermomicrostructural model calculates the mean flow stress taking into account accumulated strain between passes to incorporate the effect of the static, dynamic and metadynamic recrystallization. This thermomicrostructural model also allows the calculation of the austenite grain size between passes and the ferrite grain size after the steel leaves of the last stand. The model calculates the roll force in all the stands taking into consideration the effect of the strip tension between stands applied on the material during rolling mill and the work roll gap. Therefore, the material exit thickness for each stand or the material entrance thickness of the next stand can be calculated. A thermal model was developed, where the usual thermal equations were used to calculate the thermal exchanges of the steel in the hot strip mill. With this, the thermomicrostructural model can calculate the thermal, microstructural variations, mean flow stress that occurs in the steel and also the roll force, exit thickness and entry temperatures of the steel in each stand, in the hot strip mill. The model also closely agreed with the industrial data of different hot strip mills and for different types of carbon and microalloyed steels and for literature data. Then operational disturbances in the thermomicrostructural model were introduced and sensitivity curves were plotted that showed the changes that these disturbances cause in the steel properties, such as, mean flow stress, grain size, strip temperature, material exit thickness and roll force, not only in the one specific stand but also the effect in the next stands. Using the simulations, it was elaborated a group of qualitative rules that make it possible to determine which actions should be taken if the disturbances occur in the material thickness and/or entry temperature and/or mean flow stress and the corrections to be done in the manipulated variables, which are the roll gap, the strip tension between stand and the work roll speed, aiming to recover the strip thickness, improve mechanical properties and reduce roll force. It can therefore determine the priorities and measures that are needed for the mechanical properties of the material, microstructure and steel exit thickness and also the roll force as an operational parameter. These qualitative rules provide a base to develop some type of programming aimed at hot strip mill control, such as a soft computing program.